Distinct but integrated processing of lexical tones, vowels, and consonants in tonal language speech perception: Evidence from mismatch negativity. (February 2022) - Yu, Keke; Chen, Yuan; Wang, Menglin; Wang, Ruiming; Li, Li
Abstract: The processing of lexical tones, vowels, and consonants is significant in tonal language speech perception. However, it remains unclear whether their processing is similar or distinct concerning the extent and time course and whether their processing is independent or integrated. Thus in the present study, we conducted two event-related potential (ERP) experiments to explore how native speakers of Cantonese process lexical tones (including level and contour tones), vowels, and consonants in real vs. pseudo-Cantonese words with mismatch negativity (MMN). The MMN amplitudes and latencies showed that lexical tones and vowels were processed similarly in extent and time course. Lexical tones and consonants were processed differently in extent and time course. Vowels and consonants were processed to similar extents but over different time courses. Lexicality (real words vs. pseudowords) and tonal type (level vs. contour tones) modulated the differences in the extent and time courses of processing between lexical tones/vowels and consonants. The MMN additivity analyses further suggested that the processing of lexical tones and vowels, lexical tones and consonants, and vowels and consonants were integrated regardless of lexicality and tonal type. The results revealed that distinct but integrated processing occurs for lexical tones, vowels, and consonants in the speech perception of tonal languages. The findings provided neurophysiological evidence for the mechanism underlying tonal language spoken word recognition. Highlights: Lexical tones and vowels are processed similarly in terms of extent and time course. Lexical tones and consonants are processed differently in terms of extent and time course. Vowels and consonants are processed to similar extents but over different time courses. Lexical tones and vowels, lexical tones and consonants, and vowels and consonants are processed integrally. Lexicality and tonal type modulate the differences between lexical tones/vowels and consonants processing.